Blending Lime with Sugarcane Bagasse Ash for Stabilizing Expansive Clay Soils in Subgrade - Zalwango Teddy; Bazairwe Annette; Safiki Ainomugisha (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Expansive soils constitute one of the most frequently encountered and challenging soils to geotechnical engineers. This study assessed the possibility of utilizing sugarcane bagasse ash (SCBA) by partially replacing slaked lime to stabilize expansive clay soils. The soil samples were picked from Muduuma area, Mpigi district, Central Uganda. Experimental tests of linear shrinkage (LS), plasticity index (PI), and California Bearing Ratio (CBR) were conducted on both unstabilized soil and SCBA-lime treated samples. The SCBA-lime mixture was prepared by partially replacing 5% lime with SCBA at 2, 4, 6, 8, and 10% by weight. Hence, SCBA was used in proportions of 0.1, 0.2, 0.3, 0.4, and 0.5% by dry weight of the soil. The addition of lime greatly lowered the PI and LS, which later increased with the addition of the SCBA. The maximum dry density was generally lowered with the addition of lime and SCBA, from 1.87 g/cm3 to 1.58%. The CBR increased with SCBA-lime addition from 12% for unstabilized soil up to 48% at 6% SCBA replacement. The optimum lime replacement was established as 6% SCBA lime replacement based on CBR criteria. At the 6% optimum, the optimum moisture content (OMC) was 1.7 Mg/m3, LS was 10%, and PI was 20%. This study demonstrated the potentiality of SCBA as a novel construction material, specifically by partially reducing the usage of the unsustainable, non-environmentally friendly lime. It is also expected to enable using currently unsuitable clays from the region.